2018
DOI: 10.1002/cssc.201800944
|View full text |Cite
|
Sign up to set email alerts
|

Structure‐Guided Engineering of α‐Keto Acid Decarboxylase for the Production of Higher Alcohols at Elevated Temperature

Abstract: Branched-chain keto acid decarboxylases (KDCs) are a class of enzymes that catalyze the decarboxylation of α-keto acids. They are key enzymes for production of higher alcohols in vivo and in vitro. However, the two most active KDCs (KivD and KdcA) have only moderate thermostability (<55 °C), which hinders the production of alcohols at high temperatures. Herein, structure-guided engineering toward improved thermostability of KdcA is outlined. Strategies such as stabilization of the catalytic center, surface eng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
14
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 46 publications
(136 reference statements)
2
14
2
Order By: Relevance
“…As reported previously by Manfred [28] and Samuel [29], a reduction of the B-values can increase a protein's heat stability. In this approach, a reduction of the protein flexibility (entropy) and modification of the surface amino acids can increase the protein's thermostability to some extent [29]. Thus, the method of protein crystal structure analysis may have a more considerable role in enhancing the stability of thermophilic proteins.…”
Section: Introductionsupporting
confidence: 58%
See 1 more Smart Citation
“…As reported previously by Manfred [28] and Samuel [29], a reduction of the B-values can increase a protein's heat stability. In this approach, a reduction of the protein flexibility (entropy) and modification of the surface amino acids can increase the protein's thermostability to some extent [29]. Thus, the method of protein crystal structure analysis may have a more considerable role in enhancing the stability of thermophilic proteins.…”
Section: Introductionsupporting
confidence: 58%
“…In highresolution X-ray crystallographic studies of the protein, the temperature factor (B-value) is used to reflect the blurring of atomic electron densities and ambiguity of the atomic spatial state in the crystal structure [27]. As reported previously by Manfred [28] and Samuel [29], a reduction of the B-values can increase a protein's heat stability. In this approach, a reduction of the protein flexibility (entropy) and modification of the surface amino acids can increase the protein's thermostability to some extent [29].…”
Section: Introductionmentioning
confidence: 99%
“…Our previous work on evolving thermostable, branchedchain a-keto acid decarboxylase from Lactococcus lactis (LlKdcA) showed that improved thermostability was also translated to increased stability against isobutanol. 24 The direct relationship between thermostability and organic solvent stability has also been described in other enzyme classes. 21,25,26 Therefore, to save time and expense in nding PDC variants with increased thermostability and butanol-stability, we developed a simple screening platform to screen only for improved thermostability.…”
mentioning
confidence: 92%
“…7M.D). 24 As ApPDC and LlKdcA belong to the same a-keto acid decarboxylase family, we intended to (Fig. S1).…”
mentioning
confidence: 99%
See 1 more Smart Citation